Station eleven - Mandel, Emily St. John, 1979- (New York : Vintage Books, 2015)
One night an actor slumps over and dies onstage during a production of King Lear. Hours later, the world as we know it begins to dissolve. Moving back and forth in time-from the actor's early days as a film star to fifteen years in the future, when a theater troupe known as the Traveling Symphony roams the wasteland of what remains. The novel charts the fate that connect five people: the actor, the man who tried to save him, the actor's first wife, his oldest friend, and a young actress with the Traveling Symphony, caught in the crosshairs of a dangerous self- proclaimed prophet.
Keywords: Actors -- Fiction; Time travel -- Fiction; Dystopias -- Fiction; Science fiction; Adventure fiction